2008
DOI: 10.1016/j.jog.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Age of the source of the Jarrafa gravity and magnetic anomalies offshore Libya and its geodynamic implications

Abstract: International audienceThe interpretation of the Jarrafa magnetic and gravity highs, NW Libyan offshore, suggests that it may be caused by a body of high-density and high magnetization. Analysis of their power spectra indicates two groups of sources at: (1) 2.7 km depth, probably related to the igneous rocks, some of which were penetrated in the JA-1 borehole, (2) 5 km depth, corresponding to the top of the causative body and (3) 10 km depth, probably referring to the local basement depth. The boundary analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The transform essentially consists of a Reduction to Pole operation to centre the magnetic anomaly over its causative body and a vertical integration to simplify the anomaly such that the pseudogravity anomaly due to a uniformly, induced magnetised body has the same shape as the gravity anomaly due to the same uniform density body. Pseudo-gravity has been used to map contacts (Pilkington, 2007), as an alternative domain for comparing observed and modelled magnetic fields (Kimbell et al, 2010) or for direct comparison of gravity and magnetic anomalies (Reeh and Aïfa, 2008). The pseudo-gravity can be analysed and modelled in the same manner as gravity data, but it remains a magnetic anomaly and can only be interpreted in terms of magnetisation (or susceptibility as induced magnetisation is effectively assumed).…”
Section: Introductionmentioning
confidence: 99%
“…The transform essentially consists of a Reduction to Pole operation to centre the magnetic anomaly over its causative body and a vertical integration to simplify the anomaly such that the pseudogravity anomaly due to a uniformly, induced magnetised body has the same shape as the gravity anomaly due to the same uniform density body. Pseudo-gravity has been used to map contacts (Pilkington, 2007), as an alternative domain for comparing observed and modelled magnetic fields (Kimbell et al, 2010) or for direct comparison of gravity and magnetic anomalies (Reeh and Aïfa, 2008). The pseudo-gravity can be analysed and modelled in the same manner as gravity data, but it remains a magnetic anomaly and can only be interpreted in terms of magnetisation (or susceptibility as induced magnetisation is effectively assumed).…”
Section: Introductionmentioning
confidence: 99%
“…The pseudogravity is thus essentially the same as the magnetic potential for a vertical magnetic field. Pseudogravity has been used to map contacts (Fairhead et al, 2004;Pilkington, 2007), as an alternative domain for comparing observed and modeled magnetic fields (Kimbell et al, 2010) or for direct comparison of gravity and magnetic anomalies (Reeh and Aifa, 2008). The pseudogravity can be analyzed and modeled in the same manner as gravity data, but it remains a magnetic anomaly and can only be interpreted in terms of magnetization distribution.…”
Section: Introductionmentioning
confidence: 99%